2008
DOI: 10.1037/a0012833
|View full text |Cite
|
Sign up to set email alerts
|

Increasing and decreasing motor and cognitive output: A model of general action and inaction goals.

Abstract: General action and inaction goals can influence the amount of motor or cognitive output irrespective of the type of behavior in question, with the same stimuli producing trivial and important motor and cognitive manifestations normally viewed as parts of different systems. A series of experiments examined the effects of instilling general action and inaction goals using word primes, such as “action” and “rest.” The first 5 experiments showed that the same stimuli influenced motor output, such as doodling on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
171
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(184 citation statements)
references
References 50 publications
(55 reference statements)
7
171
2
4
Order By: Relevance
“…These items included "How strongly do you feel happy", "sad", "excited", and "nervous". Responses to these questions did not differ across prime or computer task conditions, Fs < 1, ns, which is consistent with prior work that has consistently found null effects on mood items based on manipulations of general action (e.g., Albarracin et al, 2008).…”
Section: Experiments Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…These items included "How strongly do you feel happy", "sad", "excited", and "nervous". Responses to these questions did not differ across prime or computer task conditions, Fs < 1, ns, which is consistent with prior work that has consistently found null effects on mood items based on manipulations of general action (e.g., Albarracin et al, 2008).…”
Section: Experiments Methodssupporting
confidence: 77%
“…Interestingly, recent empirical work has demonstrated that behavior can be guided by broad goals to engage in active or inactive behaviors, regardless of what behavior is ultimately pursued (Albarracin et al, 2008. Furthermore, these goals can be moderated by exposure to environmental stimuli that denote the concepts of action and inaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus behaviour is not only guided by reward pursuit that requires conscious information processing. For instance, implicit priming of the concepts 'action' and 'inaction' (e.g., using words primes such as active, go or rest, stop) can facilitate or impede, respectively, motor and cognitive processes in a variety of behaviours such as eating, drawing and even political participation (Albarracín et al, 2008;Albarracín et al, 2009;Noguchi et al, 2010). Here, action and inaction constructs were defined as "motivational end states that regulate the pursuit of high-effort, active behaviour versus low-effort, inactive behaviour" .…”
Section: Introductionmentioning
confidence: 99%